2021
DOI: 10.1155/2021/9916102
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Head Hemoglobin Levels in Glaucoma: A Structural and Functional Correlation Study

Abstract: Purpose. To investigate structural and functional correlations in glaucoma patients using optic nerve head hemoglobin (ONH Hb) measurements as determined by automated colorimetric analysis of conventional retinography. Methods. We prospectively enrolled healthy participants and glaucomatous patients with a wide range of disease stages. All participants underwent visual field (VF) testing (standard automated perimetry, SAP), color fundus imaging (mydriatic retinography), and peripapillary retinal nerve fiber la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…However, in the different studies, there is a notable difference in the results obtained between the Laguna-ONhE and OCT Spectralis RNFL indices. In chronic open-angle glaucoma, an equivalent diagnostic ability between the two indices has been found [ 27 ], while another study conducted in Brazil found, as in the present study, that the correlation between the two indices is poor [ 28 ]. These data may be related to racial or specific characteristics of normotensive glaucoma, as in the latter, a higher diagnostic ability of BMO-MRW vs. RNFL has been reported [ 14 ].…”
Section: Discussionsupporting
confidence: 66%
“…However, in the different studies, there is a notable difference in the results obtained between the Laguna-ONhE and OCT Spectralis RNFL indices. In chronic open-angle glaucoma, an equivalent diagnostic ability between the two indices has been found [ 27 ], while another study conducted in Brazil found, as in the present study, that the correlation between the two indices is poor [ 28 ]. These data may be related to racial or specific characteristics of normotensive glaucoma, as in the latter, a higher diagnostic ability of BMO-MRW vs. RNFL has been reported [ 14 ].…”
Section: Discussionsupporting
confidence: 66%
“…Considering structure-functional correlations in glaucoma, our group has previously shown a significant linear correlation between hemoglobin levels and OCT parameters and a significant nonlinear correlation between GDF and VF values. 23 Analyzing the GDF pattern in different glaucoma stages, we documented that the GDF values decay may precede VF changes overtime. Other studies also showed good agreement between ONH Hb and both OCT and VF, based on Octopus and Easyfield perimeters.…”
Section: Discussionmentioning
confidence: 88%
“… 22 Our group demonstrated significant associations between ONH Hb values and both structural and functional damage in glaucoma. 23 …”
Section: Introductionmentioning
confidence: 99%
“…It can detect DR lesions, including microaneurysms and minor hemorrhages (specificity of 71.4%) [95]. It can also evaluate biological aging [96] and hemoglobin on optic disc photographs [97] RetinAI transparency should be a concern in the application of AI-enabled technologies.…”
Section: Recommendation 1: Integration Of Meta-data and Data Setsmentioning
confidence: 99%